KARAKTERISTIK PENDERITA DIABETES MELLITUS YANG DI RAWAT JALAN DI KLINIK ALIFA DIABETIC CENTRE MEDAN TAHUN 2013-2014 - siti elsandi; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTDiabetes mellitus (DM) is the degenerative disease which the prevalence keeps increasing. Based on International Diabetes Federation Atlas (IDF Atlas, 2014) the prevalence of DM in Indonesia reached 5,8%. Based on Kemenkes in 2013, the proportion of DM in North Sumatra reached 2,3%. The aim of this research is to find out the characteristics of the DM outpatients at Alifa Diabetic Centre Clinic Medan from 2013 to 2014.This study is descriptive by using case series design. The population were 433 outpatients of DM in Alifa Diabetic Centre Clinic Medan from 2013 to 2014. The sample size were 207 cases by using simple random sampling. The data analysis uses a secondary data by using Chi-Square and Fisher’s Exact.The results of this research showed that the highest proportion of patient with DM was at the age group 55-63 years is male (10,6%) and women (19,8%), Muslim (74,4%), unemployee (37,7%), staying of Medan Maimun district (67,1%), married (86,5%), the family history of disease (64,7%), type 2 DM (97,6%), ≤6 visits in a year (78,8%), with complications (59,4%), complication of diabetic neuropathy (41,9%), ≤5 year (55,2%), OHO (75,4%) and the bad end of KGD (86,7%). According to the statistical test with Exact Fisher, there was significant differences between age by the type of DM (p = 0,000). There was no significant differences between the gender by the type of DM (p = 1,000), the types of complications by the type of DM (p = 0,155), the age by the types of complications (p = 0,099), gender by the types of complications (p = 0,521), occupation by the types of complications (p = 0,334) and the type of complications by the long history of diabetes (p = 0,051). The results of statistical test by Chi-Square between KGD end by long history of diabetes and KGD end based on the number of visits in a year could not be done because there were 4 cells (66,7%) with expected counts which were less than 5.It is expected for the clinic to use HbA1C test methods to control blood sugar levels in diabetic patients. The patients with DM in the clinic should have a healthy diet and lifestyle in their daily life at home and environment around.Keywords : Diabetes Mellitus, Characteristic, Alifa Diabetic Centre Clinic